Conveying linguistic interference in american multicultural literature translation (Eurasian Journal of Philology Science and Education, 2025)
The present paper explores the understudied area of translating texts that reflect cultural and linguistic pluralism. The article examines how linguistic interference such as code-switching, code-mixing, and contaminated speech manifests in American multicultural literature and how these elements are conveyed in literary translation. The methodological framework of the study involves linguacultural analysis, complex sampling, and translation analysis, which together facilitate the identification of interference types and the assessment of the adequacy of various translation strategies in preserving the authenticity of characters and the original structure of the text. A key focus is the linguacultural analysis of the pragmatic and stylistic functions of interference as expressive devices in the source multicultural text and their translation equivalents in the target text. The results emphasize the significance of adaptive translation solutions, such as transliteration with parallel translation, contextual adaptation, and other techniques that strike a balance between preserving foreign cultural elements and adapting them for the target linguaculture. The paper contributes to the study of linguacultural aspects of fiction translation and the development of approaches that ensure the preservation of cultural diversity and textual authenticity during translation, that is especially relevant in the context of cultural globalization.Keywords: linguacultural translation, American multicultural literature, linguistic interference, code-switching, bilingualism, foreignization, domestication.